Radiation-induced brain injury: current concepts and therapeutic strategies targeting neuroinflammation. Issue 1 (5th May 2020) - Turnquist, Casmir; Harris, Brent T; Harris, Curtis C
Abstract: Continued improvements in cancer therapies have increased the number of long-term cancer survivors. Radiation therapy remains one of the primary treatment modalities with about 60% of newly diagnosed cancer patients receiving radiation during the course of their disease. While radiation therapy has dramatically improved patient survival in a number of cancer types, the late effects remain a significant factor affecting the quality of life particularly in pediatric patients. Radiation-induced brain injury can result in cognitive dysfunction, including hippocampal-related learning and memory dysfunction that can escalate to dementia. In this article, we review the current understanding of the mechanisms behind radiation-induced brain injury focusing on the role of neuroinflammation and reduced hippocampal neurogenesis. Approaches to prevent or ameliorate treatment-induced side effects are also discussed along with remaining challenges in the field.